Investigação da poluição por metais tóxicos no córrego do Cintra - Belluta, Ivalde [UNESP]; Celho, José Carlos [UNESP]; Silva, Ramon Felipe Bicudo; Carvalho, Lídia Raquel de [UNESP]; Silva, Assunta Maria Marques da [UNESP]; Valente, José Pedro Serra [UNESP] (My University, 2014)
Cintra stream is the major receiver of treated effluent from sanitary, hospital and research laboratory sewage from the UNESP campus in Botucatu, Rubião Júnior District, São Paulo state; and it has shown evidence of diffuse contamination by metals along it. Analyses of the most toxic metals (Pb, Cu, Fe, Ni and Zn) were carried out by using an atomic absorption spectrometer AA-6.800 - Perkin Elmer, analyst 700. ANOVA followed by the Tukey test were used for data analyses at 5% significance level. The main objective of this study was to compare current data on metal levels with data from other studies, in the same area, and of the same nature, conducted before and after implementation of chemical residue management by the university in 2008. Also, it aimed at identifying and quantifying possible diffuse and punctual contamination. Sites S1 and S2 showed punctual contamination, while diffuse sources were observed between S4 and S5. The quality of water in the Cintra Stream improved after establishment of the program of laboratory chemical residue management in the Campus of UNESP.
Evaluation of toxic metal pollution in the Cintra stream
Keywords: Hospital and laboratory sewage; Sub-watershed